2007
DOI: 10.1590/s1413-86702007000600017
|View full text |Cite
|
Sign up to set email alerts
|

Congenital toxoplasmosis infection in an infant born to an HIV-1-infected mother

Abstract: We report the occurrence of congenital toxoplasmosis in an infant born to an HIV infected mother who had high anti-toxoplasma IgG and negative IgM at nine weeks of gestation. We briefly review available literature and discuss the possible mechanisms of transmission of congenital toxoplasmosis among HIV infected pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…This indicates that a routine screening for not only children from HIV-infected mothers should be used to detect congenital toxoplasmosis but also in pregnant women to confirm an early diagnosis of a reactivation of a chronic Toxoplasma infection. The first case of congenital toxoplasmosis was reported in Brazil, this was from an HIV-infected mother with a high titer of IgG but negative for IgM antibodies (Cruz et al, 2007). This highlights the special attention needed for analysis of maternal titers of anti-Toxoplasma antibody during HIV prenatal care.…”
Section: Congenital Toxoplasmosismentioning
confidence: 86%
See 1 more Smart Citation
“…This indicates that a routine screening for not only children from HIV-infected mothers should be used to detect congenital toxoplasmosis but also in pregnant women to confirm an early diagnosis of a reactivation of a chronic Toxoplasma infection. The first case of congenital toxoplasmosis was reported in Brazil, this was from an HIV-infected mother with a high titer of IgG but negative for IgM antibodies (Cruz et al, 2007). This highlights the special attention needed for analysis of maternal titers of anti-Toxoplasma antibody during HIV prenatal care.…”
Section: Congenital Toxoplasmosismentioning
confidence: 86%
“…Seven of the 50 studies were conducted on HIV-infected pregnant women, 2 reported a high seroprevalence, 53.7% in Thailand (Wanachiwanawin et al, 2001) and 74% in Brazil (Cruz et al, 2007). Considering these epidemiological studies (Table 1), geographical location, environment, socio-economic, clinical and diagnostic methods are among the factors that can pin point the differences of Toxoplasma infections between these affected areas.…”
Section: Congenital Toxoplasmosismentioning
confidence: 99%
“…22,23 Moreover, IgG avidity can assist during the first trimester of pregnancy when recent maternal infection reveals low IgG avidity to indicate a high risk of congenital infection. 24 The epidemiological study on toxoplasmosis in pregnant women would be incomplete without assessing their significant risk behaviors. The seroprevalence of Toxoplasma IgG antibody in our pregnant women increased with age, [25][26][27][28] and can be explained because even though some of these countries are located in different geographical zones, we definitely share certain similarities in terms of our environment, culture, and life styles.…”
Section: Discussionmentioning
confidence: 99%
“…In our literature review, three additional cases of fetal infection due to reactivation of maternal toxoplasmosis in HIV-1-infected women were found in the last three years. 7,31,32 Our study has some limitations. The results were based on cross-sectional data from HIV-positive patients with chronic T. gondii infection who may not represent the hypothetical original cohort of patients, among whom losses were not random.…”
Section: Characteristicsmentioning
confidence: 92%